Carbonic Anhydrases: New Perspectives on Protein Functional Role and Inhibition in Helicobacter pylori - Campestre, Cristina; De Luca, Viviana; Carradori, Simone; Grande, Rossella; Carginale, Vincenzo; Scaloni, Andrea; Supuran, Claudiu T.; Capasso, Clemente (Frontiers in Microbiology, 2021)
Our understanding of the function of bacterial carbonic anhydrases (CAs, EC 4.2.1.1) has increased significantly in the last years. CAs are metalloenzymes able to modulate CO2, HCO3- and H+ concentration through their crucial role in catalysis of reversible CO2 hydration (CO2 + H2O ⇄ HCO3- + H+). In all living organisms, CA activity is linked to physiological processes, such as those related to the transport and supply of CO2 or HCO3-, pH homeostasis, secretion of electrolytes, biosynthetic processes and photosynthesis. These important processes cannot be ensured by the very low rate of the non-catalyzed reaction of CO2 hydration. It has been recently shown that CAs are important biomolecules for many bacteria involved in human infections, such as Vibrio cholerae, Brucella suis, Salmonella enterica, Pseudomonas aeruginosa and Helicobacter pylori. In these species, CA activity promotes microorganism growth and adaptation in the host, or modulates bacterial toxin production and virulence. In this review, recent literature in this research field and some of the above-mentioned issues are discussed, namely: i) the implication of CAs from bacterial pathogens in determining the microorganism growth and virulence; ii) the druggability of these enzymes using classical CA inhibitors (CAIs) of the sulfonamide-type as examples; iii) the role played by Helicobacter pylori CAs in the acid tolerance/adaptation of the microbe within the human abdomen; iv) the role of CAs played in the outer membrane vesicles spawned by H. pylori in its planktonic and biofilm phenotypes; v) the possibility of using H. pylori CAIs in combination with probiotic strains as a novel anti-ulcer treatment approach. The latter approach may represent an innovative and successful strategy to fight gastric infections in the era of increasing resistance of pathogenic bacteria to classical antibiotics.